Citrus as a component of the Mediterranean Diet - Duarte, Amílcar (2017)
Citrus are native to southeastern Asia, but are present in the Mediterranean basin for centuries. This group of species has reached great importance in some of the Mediterranean countries and, in the case of orange, mandarin and lemon trees, they found here soil and climatic conditions which allows them to achieve a high level of fruit quality, even better than in the regions where they came from. Citrus fruits are present in the diet of the peoples living on the Mediterranean basin, at least since the time of the Roman Empire. In the 20th century they became the main crop in various agricultural areas of the Mediterranean, playing an important role in the landscape, in the diet of the overall population, and also in international trade. They are present in the gardens of palaces and monasteries, but also in the courtyards and orchards of the poorest families. Their fruits are not only a refreshing dessert, but also a condiment, or even a major component of many dishes. Citrus fruits have well-documented nutritional and health benefits. They can actually help prevent and cure some diseases and, above all, they are essential in a balanced and tasty diet.